Study of efficiency of solid state ultra-bright LED as a function of temperature - Lin, Lionel HongYi. (2009)
Solid-state lighting technology based on injection electroluminescence devices, light-emitting diode (LEDs) has the ability to operate with a long life typically in the order of 50,000 to 100,000 hours. Therefore, the global lighting community has no doubt that high-power LEDs will play an important role in general lighting applications in the near future. LEDs are already being used in applications like traffic lights, automotive signage, full-colour video displays, liquid crystal display backlighting, optical measurements, and phototherapy. The most common way for white LED is to make use of the approach of a luminescence conversion LED, where blue light of a GaN Chip is somewhat converted into yellow light by a phosphor. This combination result of the not converted blue and the yellow light will result in white light. The goal of this study is to understand what affects the efficiency of ultra-bright white LEDs. This study is based on Osram Platinum DRAGON warm white. It is known that the key element of LED‟s efficiency and reliability is decided by junction temperature. Junction temperature can to a degree affect many LED constants such as forward voltage, peak emission wavelength and thereby colour, spectral line width, and the dynamics of the degradation process. Thus LEDs are run at elevated junction temperature to study the changes in optical parameters of high power LEDs at different temperatures. White over blue ratio (W/B) based method is used to justify the junction temperature in this study. Overall efficiency of LEDs will decrease with increased junction temperature. In the final part of the report, the causes of the decline of efficiency are studied. Results show the heat affects the efficiency in one way or another.